Building the Foundation of Financial Behavior among MSMEs in Medan An Analysis of the Roles of Financial Literacy, Financial Attitude, and Financial Inclusion - Perangin-Angin, Naca; Ginting, Litka Tiadoraria Br; Ginting, Sugianta Ovinus (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the influence of financial literacy, financial attitude, and financial inclusion on the financial behavior of MSMEs in Medan. Using a quantitative method with Structural Equation Modeling (SEM), data were collected from 100 MSMEs. The results show that financial literacy and financial inclusion do not significantly affect financial behavior. In contrast, financial attitude has a significant positive effect. These findings suggest that behavioral changes in MSMEs are more driven by internal attitudes than by financial knowledge or access. Therefore, financial training should not only focus on knowledge and access, but also on shaping positive financial mindsets among MSME actors.